EFFECT OF SOIL TYPE AND DIFFERENT SHADE LEVELS ON RESULTS OF Asystasia gangetica (L) subsp. Micrantha AT SECOND SHOOTING - J.R.G., Hutapea,; Witariadi, N.M.; Wirawan, I W. (Jurnal Peternakan Tropika; Vol 12 No 6 (2024): Vol. 12 No. 6 Year 2024; November - Desember, 2024)
Forage is a source of feed ingredients for ruminants to increase livestock productivity. One type of plant that can be given to ruminants is Asystasia gangetica (L) subsp. Micrantha. The study aimed to determine the interaction and effect of soil type and different levels of shade on the yield of Asystasia gangetica plants in the second cutting. This research was conducted in Sading Village, Mengwi District, Badung Regency. This study lasted 10 weeks, the experiment used a complete randomized design (CRD) split splot pattern. The main plot was soil type: mediteran soil (TM), latosol soil (TL), and regosol soil (TR) and the sub plot was the level of shade: N1: 20%, N2: 40%, and N3: 60%. From these 2 factors, 9 treatments were obtained and each treatment was repeated 3 times, so there were 27 experimental units. The treatments are: TMN1, TMN2, TMN3, TLN1, TLN2, TLN3, TRN1, TRN2, and TRN3. The observed variables were yield variables and plant growth characteristics. The results showed that there was an interaction in the variable ratio of total dry weight of forage to dry weight of roots. It can be concluded that there is an interaction between soil types and different shade levels on leaf dry weight, stem dry weight, root dry weight, and total forage dry weight, Regosol soil and 40%  shade level tend to give the best results on Asystasia gangetica plants at the second cutting.